Proses Produksi Pembuatan Door Trim Menggunakan Mesin Injection Molding Pada PT. XYZ - Suparya; Ratna Dewi Anjani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In this study, the production process of moulded doors using an injection moulding machine at PT. XYZ. The aim of this research is to determine and analyse the efficiency and quality of door closer production and the factors that influence the final product. PT. XYZ uses an injection moulding machine which has the advantage of high production capacity and efficient use of materials. However, there are often several problems related to product quality and quantity caused by incorrect machine settings, varying raw material quality, as well as sub-optimal conditions and moulds. This study uses data from the July door moulding production results, which totalled 48,624 units. The average cycle time for door panel production is approximately 0.217 minutes per unit. Recommended improvement measures include optimising machine settings, improving raw material quality, better mould design, operator training, manufacturing environment management and reducing manufacturing process variables. By implementing these improvements, PT. In order to compete in a highly competitive market, PT. XYZ is expected to improve the quality and efficiency of its production